A Scalable Domain Decomposition Method for Ultra-Parallel Arterial Flow Simulations (Communications in Computational Physics, 2008)
Ultra-parallel flow simulations on hundreds of thousands of processors require new multi-level domain decomposition methods. Here we present such a newtwo-level method that has features both of discontinuous and continuous Galerkinformulations. Specifically, at the coarse level the domain is subdivided into severalbig patches and within each patch a spectral element discretization (fine level) is employed. New interface conditions for the Navier-Stokes equations are developed toconnect the patches, relaxing the C0continuity and minimizing data transfer at thepatch interface. We perform several 3D flow simulations of a benchmark problem andof arterial flows to evaluate the performance of the new method and investigate itsaccuracy.